PENILAIAN TAMU TERHADAP KUALITAS CAKE DI THE ZURI HOTEL PEKANBARU - Yulistina, Mutia Asti; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is entitled Guest Assessment of Cake Quality at The Zuri Hotel Pekanbaru. The formulation of the problem in this study is how guests evaluate the quality of the cake at The Zuri Hotel Pekanbaru and what are the obstacles in producing quality cake pastry at The Zuri Hotel Pekanbaru. The purpose of this study was to determine the guest's assessment of the quality of the cake at The Zuri Hotel Pekanbaru and the constraints in producing a quality pastry cake at The Zuri Hotel Pekanbaru. The method used is quantitative with descriptive analysis, data collection instruments used in this study were questionnaires and interviews. The population in this study were guests who enjoyed food at The Zuri Hotel Pekanbaru, amounting to 840 people with a research sample of 89 people. The results of the study concluded that the guest's assessment of the quality of the cake at The Zuri Hotel Pekanbaru was "high" with a percentage of 51.69% and the obstacles in producing quality pastry cakes were in the form of machine constraints, energy constraints and cake quality constraints due to the lack of cake mixing process is not good.   Keywords: Rating, Guest, quality of cake